Demand for Money in Nepal: An ARDL Bounds Testing Approach - Budha, Birendra Bahadur (NRB Economic Review, 2013)
This paper investigates the demand for money in Nepal using the Autoregressive Distributed Lag (ARDL) approach for the period of 1975-2011.The results based on the bounds testing procedure reveal that there exist the cointegration among the real money aggregates (Mr1 and Mr2 ), real income, inflation and interest rate. The real income elasticity coefficient is found to be positive and the inflation coefficient is negative. The interest rate coefficient is negative for both of the real monetary aggregates supporting the theoretical explanation. In addition, the error correction models suggest that the deviations from the long-run equilibrium are short-lived in Mr1 than Mr2 . Finally, the CUSUM and CUSUMSQ tests reveal that the Mr1 money demand function is stable, but Mr2 money demand function is not stable implying that the monetary policy should pay more attention to Mr1 than Mr2 .